MICRO, MESO, AND MACRO CONTEXTUAL FACTORS INFLUENCING SENIOR HIGH SCHOOL TEACHERS’ PREFERENCE FOR READING ACTIVITIES - Benedicta Gatri Puspaningpuri; Thomas Wahyu Prabowo Mukti (e-Journal of ELTS (English Language Teaching Society), 2026)
English teachers could choose among various teaching methods available to them, but instructional choices are often shaped by their surrounding environment. This preliminary study investigates the contextual factors affecting English teachers’ reading instruction preferences using a quantitative method with thirty-two English teachers from senior high schools in Yogyakarta as participants. Data were collected using questionnaire via Google Forms. The researchers focus on three contextual factors: micro, meso, and macro. The results revealed micro factors (x̄ = 4.01 out of 5) influenced teachers’ preferences and decisions in teaching reading, followed by macro factors (x̄ = 3.94) and meso factors (x̄ = 3.83). Participants tended to use intensive reading strategies, frequently using small group discussions, scanning and skimming, finding main ideas, and text analysis strategies, both as individual work and/or group work. The findings suggest that to optimize reading instruction and foster students’ literacy, educators, institutional leadership, and national policymakers should be more coherent and complementary.